Aerogel for oil absorption and manufacturing method thereof

KR103020339B1Active Publication Date: 2026-09-15MYONGJI UNIV IND & ACAD COOPERATION FOUND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020220179416
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2026-09-15
Estimated Expiration
2042-12-20

Smart Images

  • Figure 112022137273449-PAT00005_ABST
    Figure 112022137273449-PAT00005_ABST
Patent Text Reader

Abstract

The present invention relates to an oil-absorbing aerogel and a method for manufacturing the same. Specifically, it relates to an oil-absorbing aerogel comprising a sub-aerogel comprising a first repeating unit derived from a fiber contained in paper, a second repeating unit derived from a binder, and a third repeating unit derived from a crosslinking agent, and a method for manufacturing the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an oil-absorbing aerogel and a method for manufacturing the same, specifically to an oil-absorbing aerogel comprising a sub-aerogel comprising a first repeating unit derived from a fiber contained in paper; a second repeating unit derived from a binder; and a third repeating unit derived from a crosslinking agent, and a method for manufacturing the same. Background Technology

[0002] Paper waste (PW) utilization technology is receiving significant attention due to severe pollution, population growth, and increasing global concerns. It has been found that paper accounts for 25–40% of the urban solid waste generated worldwide annually. This massive amount of waste destroys forests, makes disposal difficult, and pollutes the environment. Therefore, it is crucial to recycle this huge amount of waste or transform it into valuable products, and various efforts have been made to address this issue. Accordingly, the reuse of paper waste (PW) as a raw material for the manufacture of bioethanol, polymer precursors, particleboard, and other products has been considered. While paper waste (PW) has many applications, including automobiles, insulation, functional applications, sound absorption, and oil sorption, using paper waste (PW) as a precursor in aerogel manufacturing is one of the most effective methods.

[0003] Aerogels are utilized in the field of oil sorption to reduce organic-inorganic and oil waste due to their high lipophilicity, low mass, high bulk porosity, and high mechanical strength.

[0004] Aerogels are traditionally manufactured through several steps, including gel preparation, gel aging, solvent exchange, and gel drying. To date, four well-known methods have been used to dry aerogels. These four drying methods are classified as high-temperature supercritical drying, low-temperature supercritical drying, external pressure drying, and freeze-drying. However, high-temperature, low-temperature, and external pressure drying have significant limitations, such as the use of high pressure, high costs due to high temperatures as well as pressure, large amounts of solvent, difficulties in bulk delivery, longer processing times, and the need for surface modifiers within the gel. In contrast, freeze-drying offers cost reduction, simplicity, environmental friendliness, and reduced processing time, as well as improved stability and aerogel performance by leading to the creation of structures with a homogeneous pore network, high porosity, and low shrinkage rates. For paper waste (PW) to be used in aerogel manufacturing, the dissolution of paper waste (PW) or modification of surface functionality is a critical component. Consequently, fundamental limitations such as the lack of porosity, mechanical brittleness, and high-density constraints of aerogels restrict the practical use of paper waste (PW) in aerogel manufacturing. However, freeze-drying is likely one of the suitable processes for using paper waste (PW) in aerogel production because it preserves the porosity, original color, shape, and size of the original aerogel better than other drying processes.

[0005] Superhydrophobic foams, exfoliated graphite, synthetic silicone aerogels, membranes, polymers, silica aerogels, and fibers have all been employed as oil sorbents. These absorbent materials have drawbacks such as mechanical brittleness, insufficient stability, low oil sorption capacity, and limited sponginess. Furthermore, they require multi-stage production processes as well as the use of hazardous solvents. Therefore, two approaches to overcome these limitations are developing porous hydrophobic media in a simple and uncomplicated manner, and optimizing the reaction environment to generate high sponginess capable of increasing stability and sorption capacity. However, the development of more active and unique porous materials, simple and low-cost manufacturing methods, and reliable porous media for oil sorption remains a challenge.

[0006] Accordingly, there was a need for sponge-type highly porous aerogels with desirable characteristics such as high porosity, low density, excellent mechanical strength, mesoporous structure, and surface functionality by developing a series of porous media using cost-effective and versatile raw materials such as paper waste (PW) and PVA. The problem to be solved

[0007] The technical problem to be solved by the present invention is to provide an oil-absorbing aerogel comprising fibers contained in paper and capable of absorbing oil and organic solvents, and a method for manufacturing the same.

[0008] However, the problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0009] One embodiment of the present invention provides an oil-absorbing aerogel comprising a sub-aerogel comprising a first repeating unit derived from a fiber contained in paper; a second repeating unit derived from a binder; and a third repeating unit derived from a crosslinking agent.

[0010] According to one embodiment of the present invention, the fiber may comprise one selected from a cellulose-based compound, a lignin-based compound, and a combination thereof.

[0011] According to one embodiment of the present invention, the binder may comprise one selected from the group consisting of polyvinyl alcohol, alginic acid, chitosan, and combinations thereof.

[0012] According to one embodiment of the present invention, the weight-average molecular weight of the polyvinyl alcohol may be 85,000 to 124,000.

[0013] According to one embodiment of the present invention, the crosslinking agent may include glutaraldehyde.

[0014] According to one embodiment of the present invention, the surface of the sub-aerogel may further include a coating layer.

[0015] According to one embodiment of the present invention, the coating layer may include a molecular structure derived from a silane compound.

[0016] According to one embodiment of the present invention, the oil-absorbing aerogel has an average pore diameter of 2 nm or more and 4 nm or less, and 1 m 2 / g More than 2m 2 / g It may have a specific surface area of ​​the following.

[0017] According to one embodiment of the present invention, the oil-absorbing aerogel has a porosity of 98% or more and 0.01 g / cm³ Above 0.06g / cm³ It may have a volume density of the following.

[0018] One embodiment of the present invention provides a method for manufacturing an oil-absorbing aerogel comprising the steps of: homogenizing a mixture comprising a paper solution containing a first repeating unit derived from a fiber contained in paper, a binder solution containing a second repeating unit derived from a binder, and a crosslinking agent solution containing a third repeating unit derived from a crosslinking agent; ultrasonically treating and heating the homogenized mixture to produce a sub-aerogel; and freeze-drying the manufactured sub-aerogel.

[0019] According to one embodiment of the present invention, the content of the paper solution may be 0.5 to 1.5 weight%.

[0020] According to one embodiment of the present invention, the content of the binder solution may be 0.25 to 1.5 weight%.

[0021] According to one embodiment of the present invention, the concentration of the crosslinking agent solution may be 0.1 to 0.7% v / v.

[0022] According to one embodiment of the present invention, the paper solution may be prepared by crushing paper and then drying it.

[0023] According to one embodiment of the present invention, the method may further include the step of forming a coating layer by coating a coating solution containing a silane compound onto the surface of the sub-aerogel.

[0024] One embodiment of the present invention provides an oil absorbent comprising the oil-absorbing aerogel. Effects of the invention

[0025] An oil-absorbing aerogel according to one embodiment of the present invention has high porosity, low density, excellent mechanical strength, a mesoporous structure, and hydrophobicity, and can absorb an excess amount of oil and organic solvents.

[0026] Through a method for manufacturing an oil-absorbing aerogel according to one embodiment of the present invention, an oil-absorbing aerogel containing fibers contained in paper, such as paper waste, can be manufactured simply and at low cost. Brief explanation of the drawing

[0027] Figure 1 shows a method for manufacturing a sub-aerogel according to one manufacturing example of the present invention. Figure 2 is an SEM image of a sub-aerogel (ad) without MTMS treatment and a PW aerogel (eh) treated with MTMS according to one experimental example of the present invention. Figure 3 shows the BET measurement of the specific surface area of ​​PW01 aerogel (containing 0.5 wt% PW, 0.25 wt% PVA, and 0.1% v / v GA) according to one experimental example of the present invention. Figure 4 shows the BET measurement of the porosity of PW01 aerogel (containing 0.5 wt% PW, 0.25 wt% PVA, and 0.1% v / v GA) according to one experimental example of the present invention. Figure 5 shows the FT-IR spectra of a sub-aerogel (a) before MTMS treatment and a PW aerogel (b) after MTMS treatment according to one experimental example of the present invention. Figure 6 shows the water contact angles of a sub-aerogel (a) before MTMS treatment and a PW aerogel (b) after MTMS treatment according to one experimental example of the present invention. Figure 7 shows the results of an absorption experiment of water and oil by an aerogel according to one experimental example of the present invention (a) and a drift test analysis of a sub-aerogel before MTMS treatment and a PW aerogel after MTMS treatment (b). Figure 8 shows the results of a compression test performed on PW01, PW02, and PW03, which were prepared with different content of PW (Paper Waste) according to one experimental example of the present invention. Figure 9 shows the results of a compression release test of PW01 aerogel according to one experimental example of the present invention. Figure 10 shows the results of thermogravimetric analysis (TGA) of PW01 aerogel according to one experimental example of the present invention. Figure 11 shows the oil absorption performance of PW01 aerogel according to one experimental example of the present invention. Figure 12 shows the effect of the content of paper waste (PW, Paper Waste) on oil absorption capacity according to one experimental example of the present invention. Figure 13 shows the effect of the content of polyvinyl alcohol (PVA) on oil absorption capacity according to one experimental example of the present invention. Figure 14 shows the effect of the concentration of glutaraldehyde (GA) on oil absorption capacity according to one experimental example of the present invention. Figure 15 shows the kinetics of the oil absorption capacity of PW01 aerogel over time according to one experimental example of the present invention. Figure 16 shows the oil absorption capacity expressed as the liquid density of PW01 aerogel according to one experimental example of the present invention. Figure 17 shows the results of an experiment on the reusability of PW01 aerogel according to one experimental example of the present invention. Figure 18 shows the results of a post-hoc analysis of PW01 aerogel using contact angle measurement according to one experimental example of the present invention. Specific details for implementing the invention

[0028] In this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0029] In this specification, "A and / or B" means "A and B, or A or B".

[0030] In this specification, "adsorption" refers to a phenomenon in which a gas or solution is adsorbed onto a solid and absorbed to form a compound or solid solution simultaneously.

[0031] In this specification, the "weight-average molecular weight" of a compound can be calculated using the molecular weight and molecular weight distribution of the compound. Specifically, as a method for measuring the weight-average molecular weight of polyarylene sulfide, a method was used in which polyarylene sulfide was dissolved in α-chloronaphthalene at a temperature of 250°C and measured through GPC (gel penetration chromatography: column temperature 210°C).

[0032] The present invention will be described in more detail below.

[0033] One embodiment of the present invention is an oil-absorbing aerogel comprising a sub-aerogel comprising a first repeating unit derived from a fiber contained in paper; a second repeating unit derived from a binder; and a third repeating unit derived from a crosslinking agent.

[0034] Appropriate contact between a first repeating unit derived from fibers contained in the paper and a second repeating unit derived from a binder can provide versatility and tensile stability, and a third repeating unit derived from a crosslinking agent can generate hydrogen bonds to strengthen the connection between the first and second repeating units and improve the toughness and durability of the aerogel.

[0035] According to one embodiment of the present invention, the oil-absorbing aerogel comprises a first repeating unit derived from a fiber contained in paper. The fiber contained in the paper may comprise one selected from a cellulose-based compound, a lignin-based compound, and combinations thereof.

[0036] The above paper may include paper waste (PW) that has already been used and discarded. The fibers contained in the paper can be applied in many fields, including automobiles, thermal insulation, sound absorption, and oil sorption, and can also be used as a precursor in the manufacture of aerogel.

[0037] According to one embodiment of the present invention, the cellulose-based compound may include cellulose and hemicellulose.

[0038] The above-mentioned cellulose-based compound is an eco-friendly material that can be continuously used in various applications and industrial fields, and is generally used in the form of an aqueous dispersion dispersed in an aqueous solvent.

[0039] According to one embodiment of the present invention, the fibers contained in the paper may include a lignin-based compound.

[0040] The above lignin-based compound can be utilized as a fluidizing agent and a water-reducing agent.

[0041] According to one embodiment of the present invention, the oil-absorbing aerogel comprises a second repeating unit derived from a binder. The binder may comprise one selected from the group consisting of polyvinyl alcohol, alginic acid, chitosan, and combinations thereof.

[0042] When diisocyanate, divinylbenzene, benzoyl peroxide, polyphenylisocyanate, kymene, sodium hydroxide, and urea derivatives are used as the binder, the ionic contact with the substrate is low, resulting in reduced sorption capacity and potentially causing corrosion. Therefore, the binder may include one selected from the group consisting of polyvinyl alcohol, alginic acid, chitosan, and combinations thereof, and preferably may include polyvinyl alcohol (PVA) as an essential component.

[0043] According to one embodiment of the present invention, polyvinyl alcohol (PVA) with a weight-average molecular weight of 85,000 to 124,000 may be used.

[0044] Polyvinyl alcohol (PVA) having a weight-average molecular weight in the above range was selected due to its biodegradability, water solubility, accessibility, and good ionic contact with the first repeating unit, and good interaction with the first repeating unit can produce an aerogel having a structure similar to a rigid fibrous porous network web by creating an intermediate complex [first repeating unit—PVA] through synergistic arrangement.

[0045] According to one embodiment of the present invention, the oil-absorbing aerogel comprises a third repeating unit derived from a crosslinking agent. The crosslinking agent may include glutaraldehyde.

[0046] The above crosslinking agent may include glutaraldehyde, isocyanide derivatives, epichlorohydrin, and bisdiazobenzidine, but it is preferable to use glutaraldehyde to strengthen the chemical bond between the first repeating unit and the second repeating unit.

[0047] According to one embodiment of the present invention, the oil-absorbing aerogel comprises a sub-aerogel including the first repeating unit; the second repeating unit; and the third repeating unit, and may further include a coating layer on the surface of the sub-aerogel.

[0048] By including a coating layer that modifies the interfacial composition of the above-mentioned sub-aerogel, stability and hydrophobicity can be improved, and the oil absorption capacity of the oil-absorbing aerogel is significantly enhanced due to the coating layer.

[0049] According to one embodiment of the present invention, the coating layer comprising the oil-absorbing aerogel may include a molecular structure derived from a silane compound.

[0050] The above silane compound may include one selected from the group consisting of methoxytrimethylsilane, methyltrimethoxysilane, trimethylchlorosilane, and combinations thereof. By including a molecular structure derived from the silane compound in the coating layer, a silane layer is formed that is covalently immobilized on the surface of the sub-aerogel, and the substitution of hydroxyl groups by silane groups is achieved. The coated sub-aerogel has a significant oil absorption capacity, which indicates that the coated sub-aerogel is hydrophobic.

[0051] According to one embodiment of the present invention, the oil-absorbing aerogel has an average pore diameter of 2 nm or more and 4 nm or less, and 1 m 2 / g More than 2m 2 / g It can have the following specific surface area.

[0052] The presence of a mesoporous structure can be confirmed from the uniformity of specific surface area values ​​and average pore diameters. Materials containing pores of a uniform diameter exhibit larger pores and can absorb more oil.

[0053] According to one embodiment of the present invention, the oil-absorbing aerogel has a porosity of 98% or more and less than 100% and 0.01 g / cm³ Above 0.06g / cm³ It can have a volume density of the following.

[0054] It can be seen that it is a high-performance aerogel from the porosity and bulk density within the above range.

[0055] One embodiment of the present invention provides a method for manufacturing an oil-absorbing aerogel comprising the steps of: homogenizing a mixture comprising a paper solution containing a first repeating unit derived from a fiber contained in paper, a binder solution containing a second repeating unit derived from a binder, and a crosslinking agent solution containing a third repeating unit derived from a crosslinking agent; ultrasonically treating and heating the homogenized mixture to produce a sub-aerogel; and freeze-drying the manufactured sub-aerogel.

[0056] Using the fibers contained in the above paper can be eco-friendly and cost-effective, and the freeze-drying method leads to simplicity and reduced time, as well as the creation of structures with a homogeneous pore network, high porosity, and low shrinkage rate, thereby improving stability and the performance of the aerogel.

[0057] According to one embodiment of the present invention, the method may include the step of homogenizing a mixture comprising a paper solution containing a first repeating unit derived from a fiber contained in paper, a binder solution containing a second repeating unit derived from a binder, and a crosslinking agent solution containing a third repeating unit derived from a crosslinking agent.

[0058] Specifically, the method includes the step of distributing and mixing paper waste (PW) powder, a binder (PVA), and a crosslinking agent (GA) in 1 ml to 100 ml of solvent, and homogenizing the mixed solution using a homogenizer at 400 to 600 rpm for 10 to 60 minutes.

[0059] According to one embodiment of the present invention, the solvent may include deionized water (DI-water).

[0060] According to one embodiment of the present invention, the acidity of the solution can be adjusted to 4 to 5. The solution may include an acidic solution, and the acidic solution may include HCl.

[0061] Adjusting the pH of the solution to 4 to 5 is intended to promote cross-linking interactions between the paper waste powder and the binder (PVA). As a result, an aerogel with appropriate flexibility and tensile strength is formed, which reinforces the paper waste (PW)-PVA bond through the formation of hydrogen bonds, thereby improving toughness, reliability, and durability.

[0062] According to one embodiment of the present invention, the method may include the step of homogenizing the mixed solution using a homogenizer at 400 to 600 rpm for 10 to 60 minutes. Preferably, the mixed solution may be homogenized using a homogenizer at 450 to 550 rpm for 20 to 40 minutes. The homogenized mixture takes the form of a gel.

[0063] According to one embodiment of the present invention, the step of manufacturing a sub-aerogel may include the step of ultrasonically treating the homogenized mixture and the step of heating.

[0064] Specifically, a sub-aerogel can be prepared by immersing the homogenized mixture (gel form) in a solution, ultrasonically treating and heating it. The solution may include a polyethylene terephthalate (PET) cast.

[0065] According to one embodiment of the present invention, the step of ultrasonically treating the homogenized mixture may be included.

[0066] Specifically, the homogenized mixture (in gel form) can be immersed in a 30 ml polyethylene terephthalate (PET) cast and sonicated for 5 to 25 minutes. Preferably, it can be sonicated for 10 to 20 minutes.

[0067] According to one embodiment of the present invention, the step of heating the ultrasonically treated mixture may be included.

[0068] Specifically, the ultrasonically treated mixture can be heated to 70 to 90 ℃ for 1 to 3 hours to produce a sub-aerogel. It is preferable to heat the ultrasonically treated mixture to 80 ℃ for 2 hours.

[0069] According to one embodiment of the present invention, the step of freeze-drying the manufactured sub-aerogel may be included.

[0070] Specifically, the step of freeze-drying the manufactured sub-aerogel may include the step of cooling the manufactured sub-aerogel and the step of freeze-drying.

[0071] According to one embodiment of the present invention, the step of cooling the manufactured sub-aerogel may be further included.

[0072] Specifically, the above-mentioned sub-aerogel can be cooled in a refrigerator for 5 to 7 hours. This is to avoid macroscopic cracks that may occur during the freezing process.

[0073] According to one embodiment of the present invention, the step of freeze-drying the manufactured sub-aerogel may be included.

[0074] Specifically, the method may further include a step of freezing the prepared sub-aerogel at minus 80°C for 4 to 6 hours. The method may also include a step of freeze-drying the prepared sub-aerogel at minus 80°C and 5 mTorr for 18 to 30 hours. Through the steps described above, a sponge-type sub-aerogel can be obtained.

[0075] According to one embodiment of the present invention, the paper solution may be prepared by crushing paper and then drying it.

[0076] Specifically, to prepare the paper solution, the method may further include the step of ultrasonically treating the paper 1 to 5 times within 8 hours and washing it with deionized water (DI-water). The method may further include the step of mechanically grinding the washed paper to mix it into pieces with a length of 0.5 to 1 mm. The method may further include the step of drying the mixed paper in a vacuum oven at 40°C for 48 hours. Afterward, the paper is distributed in a solvent together with a binder and a crosslinking agent to form a paper solution.

[0077] According to one embodiment of the present invention, the method may further include the step of forming a coating layer by coating a coating solution containing a silane compound onto the surface of the sub-aerogel.

[0078] Specifically, the oil absorption capacity can be improved by forming a coating layer on the surface of the obtained sub-aerogel by coating it with a coating solution containing a silane compound.

[0079] The above silane compound may include one selected from the group consisting of methoxytrimethylsilane, methyltrimethoxysilane, trimethylchlorosilane, and combinations thereof.

[0080] The step of forming the coating layer can be performed in a sealed glass container at 60 to 80°C containing a coating solution comprising the sub-aerogel and the silane compound. As described above, by performing the step of forming the coating layer in a sealed glass container at 60 to 80°C, the silane compound is prevented from coming into direct contact with the sub-aerogel and can be properly bonded at an appropriate temperature, thereby preserving the internal structure of the sub-aerogel.

[0081] By including a molecular structure derived from a silane compound in the coating layer formed above, a silane layer is formed that is covalently immobilized on the surface of the sub-aerogel, and the substitution of hydroxyl groups by silane groups is achieved. The coated sub-aerogel can have a significant oil absorption capacity.

[0082] According to one embodiment of the present invention, the content of the paper solution may be 0.5 to 1.5 weight%.

[0083] The oil absorption capacity can be controlled by adjusting the content of the above paper solution, and preferably, the oil absorption capacity is best when the above paper solution is contained in 0.5 weight%.

[0084] According to one embodiment of the present invention, the content of the binder solution may be 0.25 to 1.5 weight%.

[0085] If the content of the binder solution is appropriate, it has high hydrophobicity and absorbs a large amount of oil. Therefore, the oil absorption capacity can be controlled by adjusting the content of the binder solution, and preferably, the oil absorption capacity is excellent when the content of the binder solution is 0.25 to 0.5 weight%. Most preferably, it may contain 0.25 weight% of the binder solution.

[0086] According to one embodiment of the present invention, the concentration of the crosslinking agent solution may be 0.1 to 0.7% v / v.

[0087] When the concentration of the crosslinking agent solution is appropriate, it has a good sorption capacity. According to one experimental example of the present invention, it can be confirmed that oil permeability steadily decreases as the concentration of the crosslinking agent solution increases, and from this, it can be seen that the concentration of the crosslinking agent solution and the ability to absorb oil are inversely proportional. Therefore, preferably, the oil absorption ability is best when the concentration of the crosslinking agent solution is 0.1 %v / v.

[0089] Hereinafter, experimental examples will be described in detail to specifically explain the present invention. However, experimental examples according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the experimental examples described below. The experimental examples in this specification are provided to more completely explain the present invention to those with average knowledge in the art.

[0091] <Preparation Example: Preparation of PW Aerogel>

[0092] For the preparation of PW (paper waste) aerogel, PW {components of cellulose (40-44 parts by weight), hemicellulose (30-32 parts by weight), lignin (25-32 parts by weight), and extract (5 parts by weight)} was collected from a chemical laboratory and mixed to a length of 0.5-1 mm for use. Methoxytrimethylsilane (MTMS, 97%), hydrochloric acid (HCl, 37%), glutaraldehyde solution (GA, 25% in H2O), and polyvinyl alcohol (PVA, MW = 85,000-124,000; 98-99% hydrolyzed) were used.

[0093] Figure 1 illustrates the steps for preparing a sub-aerogel prior to the coating step using methoxytrimethylsilane (MTMS). As shown in Figure 1, PW (paper waste) was sonicated (three times) for less than 8 hours, carefully washed by rinsing with deionized water (DI-water), and then dried in a vacuum oven at 40°C for 48 hours. Basically, 0.5 wt% PW, 0.25 wt% PVA, and 0.1% GA v / v were distributed in 10 ml of DI-water (the pH of the solution was adjusted to 4-5 by adding HCl to promote cross-linking interactions between PW and PVA).

[0094] To obtain the gel, the above solution was homogenized using a homogenizer at 500 rpm for 30 minutes. The gel was immersed in a 30 ml polyethylene terephthalate mold and sonicated for 15 minutes, followed by heating at 80 °C for 2 hours. To prevent macroscopic cracking during the freezing stage, the sub-aerogel was chilled in a refrigerator for 6 hours. Subsequently, the sub-aerogel was frozen in a freezer (ilShinBioBase DF8503) at -80 °C for 5 hours. The solids of the frozen sub-aerogel were dried in a freeze dryer (ilShinBioBase TFD8503) at -80 °C and 5 mTorr for 24 hours.

[0095] The subsequent step of coating the coating solution onto the obtained sub-aerogel was performed at 70°C for 2 hours in a sealed glass container containing 1 ml of methoxytrimethylsilane (MTMS) to modify the interfacial composition of the sub-aerogel. Excess byproducts (HCl) and MTMS were removed from the aerogel structure using a vacuum oven without causing disintegration. A PW aerogel was prepared by coating the coating solution onto the sub-aerogel.

[0097] Methods for Measuring Physical Properties

[0098] Contact angle measurements were performed using a contact angle analyzer (SCALAR Video Loupe VL-11S) to determine the degree of hydrophobicity. Surface area and pore diameter distributions were estimated using the BET (Brunauer-Emmett-Teller) methodology (BEL, Belsorp-II analyzer). To remove contaminants, the aerogel samples were degassed in an N2 atmosphere at 120 °C for 6 hours prior to analysis. Fourier transform-infrared (FT-IR) spectra were obtained at 4000–600 cm⁻¹. -1Spectroscopic values ​​were acquired using a (THERMO-SCIENTIFIC NICOLET-iS5) spectrometer. The morphology of the aerogel was investigated using a JEOL-3010 Field Emission-Scanning Electron Microscope (FE-SEM) in conjunction with an energy-dispersive X-ray spectrometer. A universal testing machine (UTM, Lloyd LF Plus) equipped with a 1000N load cell was used for the compression test (strength measurement) and release test (flexibility measurement) of the aerogel. To investigate the thermal stability of the aerogel, thermogravimetric analysis (TGA, model SCINCO, N-1000) was performed in air at temperatures ranging from 30 to 800 °C at a heating rate of 10 °C / min. The density of the aerogel was calculated using its physical dimensions and weight, and the porosity of the aerogel was calculated using the following Equation 1.

[0099]

[0100] Here, ρ a represents the density of the aerogel, and ρ s represents the skeletal density of a solid material. The ρ of an aerogel s It was derived using the following Equation 2.

[0101]

[0102] Here, W pw is the weight fraction of PW, W pva is the weight fraction of PVA, W ga represents the weight fraction of GA. The true density of PW (ρ pw ) is 1.5 g / cm³ 3 , true density of PVA (ρ pva ) is 1.19 g / cm³ 3 , true density of GA (ρ ga ) is 1.06 g / cm³ 3 am.

[0104] <Experimental Example: Result Interpretation>

[0105] Experimental Example 1. Analysis of morphology and pore diameter of PW aerogel

[0106] Scanning electron microscope (FE-SEM, Hitachi, S-3500N) analysis was performed to determine the morphology of PW aerogels with or without MTMS treatment prepared through the preparation example.

[0107] Figure 2 is an SEM image of a sub-aerogel (ad) without MTMS treatment and a PW aerogel (eh) treated with MTMS.

[0108] According to the ad in Fig. 2, at low magnification, the PW of the sub-aerogel without MTMS treatment is uniformly spread within the sub-aerogel.

[0109] In addition, through the SEM image of the PW aerogel in Figure 2, it can be seen that a uniform MTMS layer of fibrils porous framework can help improve oil absorption by minimizing the mass transfer rate during sorption.

[0110] The specific surface area of ​​the PW aerogel was calculated using the Brunauer-Emmett-Teller (BET) method (BEL, Belsorp-11 Analyzer). Figure 3 shows the BET measurement of the specific surface area of ​​PW01 aerogel (containing 0.5 wt% PW, 0.25 wt% PVA, and 0.1% v / v GA). According to Figure 3, the PW01 aerogel is 1.33 m² 2 g -1 The BET surface of was shown.

[0111] Figure 4 shows the BET measurement of the porosity of PW01 aerogel (containing 0.5 wt% PW, 0.25 wt% PVA, and 0.1% v / v GA). According to Figure 4, the Barrett-Joyner-Halenda (BJH) curve of the aerogel's pore size distribution showed a uniform pore diameter of 3.15 nm, confirming the presence of a mesoporous structure. Materials containing pores of a uniform diameter exhibit larger pores, which would allow for more oil. Based on these results, it was concluded that a sponge-like aerogel with uniform pores was effectively produced using a simple, low-cost freeze-drying method.

[0113] Experimental Example 2. Analysis of Chemical Structure, Wetness, and Float Test of PW Aerogel

[0114] Fourier transform-infrared (FT-IR) spectroscopy was used to investigate the chemical composition and surface functionalization of the PW aerogel prepared through the preparation example.

[0115] Figure 5 shows the FT-IR spectra of the PW aerogel before (a) and after (b) MTMS treatment. From the spectra shown in Figure 5, the substitution of -OH clusters by the silane compound can be confirmed. Figure 5a is 2884–2989 cm⁻¹. -1 It shows the peak of the untreated sub-aerogel at 3157–3558 cm⁻¹, which corresponds to the CH stretching mode of CH₂ and CH⁻ compounds. -1 The peak corresponds to the -OH stretching group of the sub-aerogel. Figure 5b shows the FT-IR spectrum of the MTMS-treated PW aerogel at 2884–2989 and 3157–3558 cm⁻¹. -1 The intensity of the peak at 1645–1783 cm⁻¹ decreased as a result of the interaction between silanol and free hydroxyl groups, which formed a silane layer immobilized on the surface via covalent bonding; consequently, substitution of -OH groups by silane groups occurred.-1 The peak coincides with the PW aerogel C=O stretching vibration. The CH2 bonding vibration of the silane group is 1372 cm⁻¹. -1 At the peak, the Si-CH3 stretching vibration is 1252 cm⁻¹ -1 It is the peak at 1015 and 844 cm -1 The peaks show the stretching vibrations of Si-O-Si and Si-C, respectively. FT-IR measurements showed 3157–3558 cm⁻¹ after MTMS treatment. -1 The decrease in the magnitude of the PW aerogel peak suggests that the -OH group was replaced by a silane group. This indicates that the silane group was successfully coated on the aerogel.

[0116] Figure 6 shows the water contact angles of a sub-aerogel (a) before MTMS treatment and a PW aerogel (b) after MTMS treatment according to one experimental example of the present invention.

[0117] The contact angle is an interfacial inspection tool used to determine whether a material can absorb or reject liquid. The water contact angles for sub-aerogel (a) and PW aerogel (b) (area 1 × 1 cm, height 10 mm, thickness 3 mm) were measured using a small glass syringe with room temperature immersion water (5 μL) as shown in Fig. 6 (ab). As shown in Fig. 6 a, the water contact angle of the sub-aerogel not treated with MTMS indicates that the water droplet was completely absorbed by the aerogel for about 1 to 5 seconds, indicating that the sub-aerogel is hydrophilic. On the other hand, as shown in Fig. 6 b, the PW aerogel treated with MTMS showed no water absorption at all, which indicates that the PW aerogel has hydrophobic properties as a result of the MTMS being homogeneously distributed within the sponge-like sub-aerogel structure and the -OH groups being significantly substituted. The water contact angle of the sub-aerogel before MTMS intervention is 0, but the water contact angle of the PW aerogel after MTMS intervention is significantly higher (147.20˚), indicating that the -OH groups have been substituted with silane groups. Theoretically, the wettability of an aerogel is defined by the sorption of water molecules onto the aerogel. A high water contact angle suggests oil sorption, which demonstrates the hydrophobicity of the aerogel. Therefore, the results for the MTMS-treated PW aerogel show that it possesses a significant oil absorption capacity, which indicates that it is hydrophobic.

[0118] Figure 7 shows the water and oil absorption experiment by the aerogel (a) and the drift test analysis of the sub-aerogel before MTMS treatment and the PW aerogel after MTMS treatment (b).

[0119] As shown in Fig. 7a, water and oil absorption by the aerogel is observed both before and after MTMS treatment. In Fig. 7b, drift test analyses were performed on the sub-aerogel before MTMS treatment and the PW aerogel after MTMS treatment to support the water contact angle results. The PW aerogel after MTMS treatment floated on the water surface for more than 48 hours, indicating that the homogeneous hydrophobic coating of silane was effectively realized. In contrast, the sub-aerogel before MTMS treatment was completely submerged in water, confirming that it possesses maximized hydrophilicity.

[0120] Consequently, PW aerogels with low density, mechanical stability, and high lipophilicity absorb more excess oil than materials with low hydrophobicity, mechanical strength, and high density. These results are consistent with water contact angle measurements and demonstrate that MTMS-treated PW aerogels are lipophilic materials.

[0122] Experimental Example 3. Confirmation of mechanical properties of PW aerogel

[0123] The mechanical properties of the PW aerogel prepared through the manufacturing example were investigated. The aerogel samples were used with a load of 2 mm / min, material compression of 90%, and release of 50% of the thickness.

[0124] Figure 8 shows the results of compression tests performed on PW01, PW02, and PW03 prepared with different PW contents. Compression tests were completed at room temperature for PW concentrations ranging from 0.5 to 1.5 wt%. Under these conditions, it was ultimately determined that density and PW content affect the elastic modulus. At a PW concentration of 0.5 wt% (PW01), the elastic modulus was 0.31 MPa. The maximum elastic modulus with allowable stiffness was 2.30 MPa, observed at a PW concentration of 1.5 wt% (PW03), suggesting that PW concentration is closely related to the elastic modulus. The most likely explanation for these findings is the inclusion of PVA, which increases the degree to which crossing fibrous network sites are supported by intermolecular interactions, as shown in Figure 8.

[0125] Aerogel compression analysis was performed to back up the results of the decompression verification. Figure 9 shows the results of the decompression test of PW01 aerogel. As shown in Figure 9, the PW01 aerogel possesses versatility and tensile stability through the appropriate contact of PW and PVA, which was found to generate hydrogen bonds to strengthen the PW-PVA connection and improve the aerogel toughness and durability.

[0127] Experimental Example 4. Confirmation of Thermal Stability of PW Aerogel

[0128] To confirm the thermal stability of the PW aerogel prepared through the preparation example, thermal properties were analyzed using thermogravimetric analysis (TGA, Sinco N-1000).

[0129] Figure 10 shows the results of thermogravimetric analysis (TGA) of PW01 aerogel. The hydrophobic properties of PW01 aerogel prevent significant weight loss up to 100 °C. The degradation pattern of PW01 aerogel was observed during two major weight loss periods. The substantial PW and PVA composition leads to the high thermal stability of PW01 aerogel. Due to the presence of PVA in PW01 aerogel, initial weight loss was observed at 180 °C. Furthermore, as shown in Figure 10, a subsequent reduction occurred around 280–480 °C, resulting in a weight loss of nearly 90%. Consequently, PW degradation occurs at high temperatures; PW01 aerogel containing PW possesses not only high heat resistance due to the strong bonding between PW and PVA but also excellent packing efficiency and lipophilic properties. PW aerogels are often thermally more stable than plastic or silica aerogels at temperatures above 400 °C.

[0131] Experimental Example 5. Derivation of Oil and Organic Solvent Absorption Capacity of PW Aerogel

[0132] PW01 aerogel is very effective in terms of oil absorption under ideal reaction conditions. The hydrophobicity of PW aerogel is increased by the MTMS process.

[0133] Figure 11 shows the oil absorption performance of PW01 aerogel. To verify the oil and organic solvent absorption capacity of PW01 aerogel in Figure 11, successive absorption experiments of oil (pump and soybean oil) and organic solvents (hexane, toluene, and chloroform) were performed on a stainless steel plate. To enhance visibility, 20 mL of oil was added to the plate, followed by the addition of a small amount of dye (Sudan Red). Subsequently, a 2 × 2 cm piece of PW01 aerogel was slowly immersed in the oil and swirled at 25 °C until equilibrium was reached. A sample of PW01 aerogel was taken, excess oil was removed, and the weight of PW01 aerogel was calculated. The oil and organic solvent sorption capacity (Q) and the theoretical mass-based sorption capacity of PW01 aerogel were derived using Equations 3 and 4.

[0134]

[0135] Here, Q max (g / g) is the absorption capacity of the PW aerogel for oils and organic solvents, and Mw(g) and Md(g) are the weights of the PW aerogel after and before absorption, respectively. The reusability of the PW aerogel was evaluated by repeating each absorption test three times, and Q max The average value of was calculated.

[0136]

[0137] Here, φ is the porosity of the PW aerogel, and ρ liq is the density of the oil and solvent (hexane toluene, chloroform, pump, and soybean oil), and ρ a is the density of the PW aerogel.

[0139] Experimental Example 6. Evaluation of the sorption capacity of PW aerogel

[0140] The absorption capacity of PW01 aerogel is determined by the aerogel's hydrophobicity, uniform porosity, density, mechanical strength, and oil interaction. Therefore, to verify the effects of PW, PVA, and GA on oil sorption capacity, various PW aerogels were prepared and their capabilities were measured. Table 1 below shows PW, PVA, and GA content This shows the density, porosity, and pump fluid absorption capacity of various PW aerogels manufactured differently.

[0141] item PW content (weight%) PVA content (weight%) GA concentration (v / v%) Density (ρ) a) (g / cm³) Porosity (φ) (%) Pump fluid absorption capacity (g / g) PW01 0.5 0.25 0.1 0.0114 99.95 57.66 PW02 1.0 0.25 0.1 0.0192 99.86 42.31 PW03 1.5 0.25 0.1 0.0274 99.73 28.20 PW04 0.5 0.5 0.1 0.0369 99.84 20.86 PW05 0.5 1.0 0.1 0.0484 99.78 15.71 PW06 0.5 0.5 0.1 0.0531 99.75 14.58 PW07 0.5 0.25 0.3 0.0257 99.85 31.29 PW08 0.5 0.25 0.5 0.0344 99.74 23.07 PW09 0.5 0.25 0.7 0.0401 98.64 19.57

[0143] The effect of PW content can be seen through PW01 to PW03 in Table 1 above, where the absorption capacity steadily decreased from PW01 to PW03. A possible explanation is the adhesion tendency of the aerogel activity to oil as well as the high-density backbone, and consequently, the PW03 aerogel has a higher density and lower porosity.

[0144] Figure 12 shows the effect of the content of paper waste (PW, Paper Waste) (2 x 2 PW aerogel samples) on the oil absorption capacity of 20 ml of oil (hexane, toluene, chloroform, pump oil, and soybean oil) at 25°C.

[0145] When PW01 aerogel was used, as shown in Fig. 12, the sorption volume for chloroform (109.33 g / g) was the highest and the absorption of hexane (48.05 g / g) was the lowest. However, when PW02 and PW03 aerogels were used as absorbents, the major difference across various PW contents directly affected oil permeability by increasing the density of the aerogel and lowering the porosity, thereby reducing the free space in the aerogel channels. This clearly demonstrates that a large amount is incompatible with oil permeability. Consequently, it can be seen that the lower the PW content, the better the oil absorption capacity.

[0146] In Table 1 above, the absorption capacity of PW04, PW05, and PW06 aerogels was investigated to evaluate the effect of polyvinyl alcohol (PVA) content. Figure 13 shows the effect of polyvinyl alcohol (PVA) content (2 x 2 PW aerogel samples) on oil absorption capacity using 20 ml of oil (hexane, toluene, chloroform, pump oil, and soybean oil) at 25°C. The oil absorption capacity of the aerogels increases in the order of PW06 (low) < PW05 (moderate) < PW04 (strong). Since the PW06 aerogel has a high density, the possibility of oil sorption is low. When PVA is mixed in a high content as in PW06, the aerogel sorption capacity decreases significantly from 20.86 g / g to 14.58 g / g. PW06 aerogel has a low oil retention capacity because it has a high density and low sponginess. Similarly, due to changes in the PVA content within the aerogel, the oil absorption performance of PW05 aerogel was found to be higher than that of PW06 aerogel. When the oil sorption of PW04 aerogel was tested using the same experimental parameters, the absorption capacity increased to 20.86 g / g as the PVA content decreased compared to PW05. From this, it was found that PW04 has very favorable oil permeability at a limited PVA content, which improves the porous structure and reduces the density of the aerogel.

[0147] The decrease in absorption performance from 20.86 g / g to 14.58 g / g in PW06 aerogel compared to PW04 aerogel is a result of more than just an increase in the PVA concentration within the aerogel. This is possible only when additional hydrophilic properties capable of reducing interaction with oil are included in the aerogel, and it is believed that this led to a decrease in oil absorption. On the other hand, the low sponginess of PW06 aerogel resulted in the appearance of a high-density network due to PVA aggregation, which reduced oil absorption capacity. Consequently, the oil absorption of PW06 aerogel decreases because oil does not bind to it. Therefore, when the concentration of PVA is appropriate, it exhibits high hydrophobicity and absorbs a large amount of oil. These characteristics of the aerogel are significantly improved by high porosity, low density, and external chemistry, as shown in Fig. 13.

[0148] The effect of % v / v of glutaraldehyde (GA) was studied through PW07 to PW09 in Table 1 above. Figure 14 shows the effect of % v / v of glutaraldehyde (GA) (2 x 2 PW aerogel samples) on oil absorption capacity using 20 ml of oil (hexane, toluene, chloroform, pump oil, and soybean oil) at 25°C. When the % v / v of GA is appropriate, it has a good sorption capacity. As the amount of GA increased, oil permeability steadily decreased. Based on these findings, it can be seen that the % v / v of GA is inversely proportional to the oil absorption capacity, as shown in Figure 14.

[0149] Figure 15 shows the kinetics of the oil absorption capacity of 2 x 2 PW01 aerogel samples over time for 20 ml of oil (hexane, toluene, chloroform, pump oil, and soybean oil) at 25°C. In Figure 15, PW01 aerogel was used for the time-dependent oil absorption kinetics. During the study, oil permeability varied depending on the viscosity and density of the oil. Among organic solvents, hexane reached absorption equilibrium more quickly because it has low viscosity and wide pores that are easily accessible. The sorption equilibrium of pump oil and soybean oil appeared gradual because the oil viscosity is high and it is difficult to completely fill the aerogel pores. This is because air occupies a portion of the aerogel volume. To support this claim, the oil sorption efficacy was investigated with respect to oil density and is shown in Figure 16.

[0150] Figure 16 shows the oil absorption capacity of 2 x 2 PW01 aerogel samples, expressed as liquid density, for 20 ml of oil (hexane, toluene, chloroform, pump oil, and soybean oil) at 25°C. As shown in Figure 16, it was found that the absorption capacity is also affected by oil density. This finding corresponds to oil sorption kinetics, which demonstrates that PW01 aerogel is particularly strong in terms of oil sorption.

[0151] The synthesized PW01 aerogel was successfully used for the absorption of various oils and organic solvents. Under optimal reaction conditions, it exhibited the greatest absorption capacity for different oils, ranging from approximately 49 to 110 times its own mass. Table 2 below compares the oil absorption capabilities of aerogels prepared using various samples. In Item 1 of Table 2, carbon aerogel was used for oil absorption, but the results showed reduced oil absorption capacity due to its high density and low water contact angle. In Item 2 for the oil absorption investigation, the use of polystyrene / magnetite (Fe3O4) / graphene aerogel resulted in reduced oil absorption due to the aerogel's weak mechanical properties. When using polystyrene monoliths in Item 3, low oil absorption was observed because the rigidity and low hydrophobicity of the polystyrene monoliths hindered interaction between the oil and the aerogel. Additionally, in Item 4, while the use of graphene oxide foam improved oil absorption performance due to its high porosity and low density, the overall oil absorption performance remained low due to the aerogel's low water contact angle. However, in the case of the PW01 aerogel of Item 5, the uniform coating of MTMS exhibited high hydrophobicity (147.20˚), high porosity (99.95%), and low density (0.0114 g / cm³). 3 It exhibits ) and high mechanical strength. Due to the synergistic combination of all parameters, the oil and organic solvent absorption performance was higher. Finally, it was found that the oil absorbent containing the generated PW01 aerogel has high oil absorption capacity.

[0152] item Sample name Building blocks menstruum Preparation method Oil absorption capacity 1 carbon aerogel Winter melon water freeze-dried 25.0 2 Polystyrene / magnetite (Fe3O4) / graphene aerogel Styren EDA freeze-dried 40.0 3 Polystyrene monolith Styren water Natural drying 16.49 4 Graphene oxide foam graphene oxide water freeze-dried 99.0 5 PW01 paper water freeze-dried 109.33

[0154] Since the reuse of aerogel is very important from an industrial perspective, the possibility of reusing aerogel was tested. PW01 aerogel was reused 15 times for oil absorption under similar reaction conditions. PW01 aerogel was recycled to evaluate stability by removing the absorbed oil by hand compression and then reusing it under the same reaction conditions.

[0155] Figure 17 shows the results of an experiment on the reusability of PW01 aerogel using 20 ml of oil (pump fluid) at 25°C. As shown in Figure 17, PW01 aerogel exhibits excellent oil absorption performance of up to 15 times due to its interconnected fibrous pore network structure with strong mechanical strength. Although PW01 aerogel was highly durable, the absorption rate decreased with each use due to the silane covering potential losses upon compression.

[0156] Figure 18 shows the results of a post-hoc analysis of PW01 aerogel using contact angle measurements. The results regarding the reusability of PW01 aerogel were confirmed through a post-hoc analysis of PW01 aerogel using contact angle measurements. As shown in Figure 18, the total contact angle decreased from 147.20 to 133.10˚. Based on the presented analysis results, it was determined that the generated PW01 aerogel is sufficiently stable and effective in terms of oil immersion.

[0158] Accordingly, the oil-absorbing aerogel and the method for manufacturing the same according to one embodiment of the present invention can contribute to excessive oil absorption by successfully producing a number of hydrophobic and sustainable aerogels from low-cost environmental paper waste (PW) for oil absorption through a simple freeze-drying approach, thereby causing a synergistic effect of PW, PVA, and GA.

Claims

Claim 1 A sub-aerogel comprising a first repeating unit derived from a fiber contained in paper; a second repeating unit derived from a binder; and a third repeating unit derived from a crosslinking agent, wherein the binder comprises one selected from the group consisting of polyvinyl alcohol, alginic acid, chitosan, and combinations thereof, and the crosslinking agent comprises glutaraldehyde, and further comprising a coating layer on the surface of the sub-aerogel comprising a molecular structure derived from a silane compound, having a porosity of 98% or more and 0.01 g / cm³ Above 0.06g / cm³ Oil-absorbing aerogel having a bulk density of the following. Claim 2 In claim 1, the fiber is an oil-absorbing aerogel comprising one selected from a cellulose-based compound, a lignin-based compound, and a combination thereof. Claim 3 delete Claim 4 An oil-absorbing aerogel according to claim 1, wherein the weight-average molecular weight of the polyvinyl alcohol is 85,000 to 124,000. Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 In claim 1, an average pore diameter of 2 nm or more and 4 nm or less, and 1 m 2 / g More than 2m 2 / g Oil-absorbing aerogel having the following specific surface area. Claim 9 delete Claim 10 A method for manufacturing an oil-absorbing aerogel comprising: a step of homogenizing a mixture comprising 0.5 to 1.5 weight% of a paper solution containing a first repeating unit derived from a fiber contained in paper, 0.25 to 1.5 weight% of a binder solution containing a second repeating unit derived from a binder, and 0.1 to 0.7% v / v of a crosslinking agent solution containing a third repeating unit derived from a crosslinking agent; a step of ultrasonically treating and heating the homogenized mixture to produce a sub-aerogel; a step of freeze-drying the produced sub-aerogel; and a step of forming a coating layer by coating a coating solution containing a silane compound on the surface of the sub-aerogel, wherein the binder comprises one selected from the group consisting of polyvinyl alcohol, alginic acid, chitosan, and combinations thereof, and the crosslinking agent comprises glutaraldehyde, and further comprising a coating layer having a molecular structure derived from a silane compound on the surface of the sub-aerogel. Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 In claim 10, the paper solution is a method for manufacturing an oil-absorbing aerogel, wherein the paper is prepared by crushing and drying paper. Claim 15 delete Claim 16 An oil absorbent comprising an oil-absorbing aerogel according to any one of paragraphs 1, 2, 4, or 8.

Citation Information

Patent Citations

  • A polysaccharide aerogel

    US20190282988A1

  • Organic-inorganic aerogel composites, methods and uses thereof

    WO2019147183A1